Enacting the 'true self': Towards a theory of embodied authentic leadership - Ladkin, Donna; Taylor, Steven S. (Elsevier Science B.V., Amsterdam., 2010)
This paper argues that although authentic leadership may be rooted in the notion of a ‘true self’, it is through the embodiment of that ‘true self’ that leaders are perceived as authentic or not. In making this claim, we consider ways in which a somatic sense of self contributes to the felt sense of authenticity, and how through engaging with somatic cues, leadership can be performed in a way which is experienced as authentic, both to the leader and to those he or she seeks to lead. In developing our ideas further, we draw from the acting theory of Stanislavski (1936a, 1936b, 1961) to explore how authentic dramatic performances are created, focusing on the role of emotional memory, the magic ‘if’ and physical aspects of performances. We propose three key components of a resulting theory of how embodied authentic leadership is created: self exposure, relating, and making leade
Keywords: MT=LEAD; Authentic leadership; Authenticity; Embodiment; Embodied leadership; Aesthetic leadership